Sistema de envasado de líquidos modelado con redes de Petri y simulado con LabVIEW y DSC (2011)
In recent decades, research groups, have been using simulation tools to validate their development, before actual testing, the results are quite acceptable and give permission or not to continue a project. Simulation software tools there are many, but we are using LabVIEW and DSC (National Instruments) because its programming environment is friendly and widely used in the automatic. The work shown below, is the development of an application focused on the fault diagnosis, by implementing a systematic algorithm, builted using the modeling tool known as “Petri Nets (MOP)”, which the main target is to make a contribution in the field of industrial safety, avoiding economic losses, estimated in damage to equipment and most important to preserve the physical integrity of human operators. The content illustrates the simulation in LabVIEW of a liquid packaging process and the implementation of their diagnoser using Petri Nets, in order to evaluate the normal and fault behavior offered by the process. Designing a communication platform and man machine interface, which is carried out monitoring, control and supervising system of way on-line.